Angiogenic Secretion Profile of Valvular Interstitial Cells Varies With Cellular Sex and Phenotype - Nelson, Victoria; Patil, Vaidehi; Simon, LaTonya R.; Schmidt, Kelsey; McCoy, Chloe M.; Masters, Kristyn S. (Frontiers in Cardiovascular Medicine, 2021)
Angiogenesis is a hallmark of fibrocalcific aortic valve disease (CAVD). An imbalance of pro- and anti-angiogenic factors is thought to play a role in driving this disease process, and valvular interstitial cells (VICs) may act as a significant source of these factors. CAVD is also known to exhibit sexual dimorphism in its presentation, and previous work suggested that VICs may exhibit cellular-scale sex differences in the context of angiogenesis. The current study sought to investigate the production of angiogenesis-related factors by male and female VICs possessing quiescent (qVIC) or activated (aVIC) phenotypes. Production of several pro-angiogenic growth factors was elevated in porcine aVICs relative to qVICs, with sex differences found in both the total amounts secreted and their distribution across media vs. lysate. Porcine valvular endothelial cells (VECs) were also sex-separated in culture and found to behave similarly with respect to metabolic activity, viability, and tubulogenesis, but male VECs exhibited higher proliferation rates than female VECs. VECs responded to sex-matched media conditioned by VICs with increased tubulogenesis, but decreased proliferation, particularly upon treatment with aVIC-derived media. It is likely that this attenuation of proliferation resulted from a combination of decreased basic fibroblast growth factor and increased thrombospondin-2 (TSP2) secreted by aVICs. Overall, this study indicates that VICs regulate angiogenic VEC behavior via an array of paracrine molecules, whose secretion and sequestration are affected by both VIC phenotype and sex.Moreover, strong sex differences in TSP2 secretion by VICs may have implications for understanding sexual dimorphism in valve fibrosis, as TSP2 is also a powerful regulator of fibrosis.